A Transactions Data Test of Stock Index Futures Market Efficiency and Index Arbitrage Profitability. - Chung, Y Peter (Journal of Finance, 1991)
This paper investigates the efficiency of the market for stock index futures and the profitability of index arbitrage for the Chicago Board of Trade's Major Market Index contracts. The spot value of the index is computed with transactions prices for the component shares of the index obtained from the Fitch database. The tests account for transaction costs, execution lags, and the uptick rule for short sales of stocks. Results indicate that the size and frequency of boundary violations are substantially smaller than those reported by earlier studies and have declined sharply with time.